2001
DOI: 10.1039/b100478f
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and spectroscopic characterisation of chiral meso-tetraarylmetalloporphyrins bearing meso-pentafluorophenyl groups

Abstract: The successful synthesis of 5,10,15,20-tetrakis[(R,R)-2,6-bis(1-phenylbutoxy)phenyl]porphyrin, with (R)-1-phenylbutoxy substituents on each of the eight ortho-positions, by a 2ϩ2 approach via meso-[(R,R)-2,6-bis(1-phenylbutoxy)phenyl]dipyrromethane rather than a one-pot condensation of (R,R)-2,6-bis(1-phenylbutoxy)benzaldehyde with pyrrole, is described. The synthesis has also been modified using meso-(pentafluorophenyl)dipyrromethane to prepare four further chiral porphyrins containing one, two (cis and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…However, in addition to the desired A 2 B 2 ‐porphyrins, other porphyrin byproducts were formed as a result of “scrambling” . In fact, for the dipyrrane substrates 2b and 10a , the byproducts were formed in larger amounts than the desired product (Table , entries 1 and 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in addition to the desired A 2 B 2 ‐porphyrins, other porphyrin byproducts were formed as a result of “scrambling” . In fact, for the dipyrrane substrates 2b and 10a , the byproducts were formed in larger amounts than the desired product (Table , entries 1 and 5).…”
Section: Resultsmentioning
confidence: 99%
“…Condensation reaction of functionalized dipyrranes to trans-A 2 B 2 -porphyrins (A = PFP substituent, B = R-tetrafluorophenyl substituent). However, in particular for the two amino-substituted dipyrranes in addition to the desired A 2 B 2 -porphyrins, other porphyrins were formed as by-products due to 'scrambling´, [36,37] for the dipyrranes 2b and 10a in amounts larger than the desired product (Table 3, entries 1 and 4). This observation is in accordance with a recent publication by Arunkumar and coworkers who also observed large amounts of scrambling products in the condensation reaction of 5-(4-cyanophenyl)-dipyrrane and 8a with BF 3 ·OEt 2 as catalyst.…”
Section: Full Papermentioning
confidence: 99%
“…27 Aerobic enantioselective alkene epoxidation catalyzed by chiral trans-dioxo (D4-porphyrinato) ruthenium (VI) complex was also reported. 31 Boitrel et al reported the asymmetric epoxidation of styrene derivatives and naphthalene derivatives using two different series of bisstrapped chiral iron porphyrin complexes derived from L-prolinoyl residues as catalysts. 29 A new family of porphyrin metal complexes based on chiral atropisomerism was reported as catalysts for the enantioselective epoxidation of styrene derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…30 In the year 2001, Foxon et al reported the synthesis of porphyrins by mixed condensation of pyrrole, (R,R)-2,6di(1-phenylbutoxy) benzaldehyde, and pentafluorobenzaldehyde. 31 Boitrel et al reported the asymmetric epoxidation of styrene derivatives and naphthalene derivatives using two different series of bisstrapped chiral iron porphyrin complexes derived from L-prolinoyl residues as catalysts. 32 In the year 2004, Nakagawa et al described an efficient synthesis of novel D4-symmetric chiral porphyrins and used them as catalysts in asymmetric epoxidation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Also, fluorocarbons display enhanced hydrophobicity, chemical resistance and thermal stability in comparison to their hydrocarbon counterparts [43,52]. Consequently, porphyrazines reported here can be proposed as active compounds for catalytic and photosensor applications in homogeneous media [17,18,53]. …”
mentioning
confidence: 99%